2019
DOI: 10.3390/molecules24050963
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking and β-Glucuronidase Inhibitory Potential of Indole Base Oxadiazole Derivatives

Abstract: β-glucuronidase is a lysosomal glycosidase enzyme which catalyzes the extracellular matrix of cancer and normal cells and the glycosaminoglycans of the cell membrane, which is important for cancer cell proliferation, invasion, and metastasis. Liver cancer, colon carcinoma, and neoplasm bladder are triggered by the increase of the level of β-glucuronidase activity. The most valuable structures are indole and oxadiazole which has gain immense attention because of its pharmacological behavior and display many bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…34). However, bioisosteric replacement attempt with oxadiazole proved that thiadiazole unit is preferred for stronger inhibition [206]. The strongest potency remained with 2,3-dihrdoxy substituted derivative 131 (IC 50 ¼ 0.90 mM), although 2-Cl derivative had an outlying potency.…”
Section: Indole-based Hybridsmentioning
confidence: 99%
“…34). However, bioisosteric replacement attempt with oxadiazole proved that thiadiazole unit is preferred for stronger inhibition [206]. The strongest potency remained with 2,3-dihrdoxy substituted derivative 131 (IC 50 ¼ 0.90 mM), although 2-Cl derivative had an outlying potency.…”
Section: Indole-based Hybridsmentioning
confidence: 99%
“…After that, the optimized structure of EcGUS was processed using the automatic tools in AutoDock Tools to remove the water of protein crystallization, add hydrogen atoms, and distribute Kollman charges. Considering the noncompetitive model of inhibition, we selected the grid dimensions of 60 × 68 × 66 Å 3 to include the section of the protein during docking simulations, and then it was used for docking. According to Lamarck genetic algorithm, the most favorable prediction confirmation was finally proposed.…”
Section: Molecular Docking Simulationsmentioning
confidence: 99%
“…Collectively, our findings demonstrated that the flavonoids in Mulberry bark displayed strong E. coli β-glucuronidase inhibition activity, suggesting that Mulberry bark might be a promising dietary supplement for ameliorating β-glucuronidase-mediated intestinal toxicity. diseases and drug/diet interventions via deconjugation of a variety of glucuronides into free aglycones, resulting in a relatively high local exposure of toxic compounds in the colonic mucosa [3][4][5]. One classical example is the regeneration of the active metabolite 7-ethyl-10-hydroxycamptothecin (SN38) from the O-glucuronide of SN38 (SN38G), in which β-GUS-catalyzed SN38G hydrolysis has been validated as the leading cause of the intestinal toxicity of irinotecan [6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…β-Glucuronidase (GUS), a member of the lysosomal glycosidase family, can hydrolyze the glucuronide bond at the non-reducing termini of glycosaminoglycans, thereby leading to the degradation of proteoglycans and the destruction of extracellular matrix, which ultimately facilitates tumor invasion and metastasis [3,4]. Abnormal GUS overexpression is associated with the development of various cancers, including liver cancer [5], gastric cancer [6], colon cancer [7], and pancreatic adenocarcinoma [8]. Thus, GUS has been regarded as a tumor biomarker [9,10].…”
Section: Introductionmentioning
confidence: 99%